Technological Changes among the Traditional Fishermen - Mohan, Braj; S., Bala Saraswathy; M.K., Kandoran; Thomas, Mary (Fishery Technology, 2025)
The present study was conducted to determine the technological changes and lrnpact perception among the tishermen regarding the recommended technologlml practices. The extent of technological changes in tlpractices, viz, use of cheaper wood materials for construction of fishing crafts and the use of synthetic fishing net materials were almost complete. the use of chemical wood preservatives was not adopted by any fishermen. The technological change with regard to the use of ice onboard country crafts was l.6l %. The studies reveled that experienced fishermen had low adoption scores. The low technological gap scores had significant relationship with higher investment and maintenance costs of crafts and nets and crew engaged.